2013
DOI: 10.1111/j.2047-2927.2013.00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Broad DNA methylation changes of spermatogenesis, inflammation and immune response‐related genes in a subgroup of sperm samples for assisted reproduction

Abstract: Aberrant sperm DNA methylation patterns, mainly in imprinted genes, have been associated with male subfertility and oligospermia. Here, we performed a genome-wide methylation analysis in sperm samples representing a wide range of semen parameters. Sperm DNA samples of 38 males attending a fertility centre were analysed with Illumina HumanMethylation27 BeadChips, which quantify methylation of >27 000 CpG sites in cis-regulatory regions of almost 15 000 genes. In an unsupervised analysis of methylation of all an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…The methylation of constitutive heterochromatic and promoter regions is generally associated with reduced gene transcription (Fig. 1A) (15)(16)(17)(18). Therefore, DNA methylation is a type of epigenetic modification that can effectively promote gene silencing (Fig.…”
Section: Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…The methylation of constitutive heterochromatic and promoter regions is generally associated with reduced gene transcription (Fig. 1A) (15)(16)(17)(18). Therefore, DNA methylation is a type of epigenetic modification that can effectively promote gene silencing (Fig.…”
Section: Dna Methylationmentioning
confidence: 99%
“…1B). The methyl group for this chemical modification of the DNA is donated by S-adenosyl-L-methionine (SAM) (17)(18)(19)(20)(21)(22), and the methylation reaction is catalyzed by members of the DNA methyltransferases (DNMT) family, which are classified into the following three types in mammals: DNMT1, DNMT2 and DNMT3. It was demonstrated that DNMT1, DNMT3a and DNMT3b are robustly expressed in the early embryonic stage; however, the biological functions of DNMT2 remain elusive (23-25).…”
Section: Dna Methylationmentioning
confidence: 99%
“…DAZL promoter methylated only in infertile patents [47] Global Infertile males (38) • Hypermethylation in spermatogenesis-related genes • Loss of methylation in inflammation and immune response-related genes [18] Global NOA (65) and oligoastenozoospermic (29)…”
Section: Line1mentioning
confidence: 99%
“…These epigenetic modifications can be inherited through both mitotic and meiotic divisions. Recent studies demonstrate that aberrant DNA methylation of imprinted genes and reproduction-related genes in particular might be helpful to explain unknown infertility cases [17][18][19][20][21][22]. Therefore, epigenetics appears to be a promising research area for studying idiopathic male infertility.…”
Section: Introductionmentioning
confidence: 99%
“…However, methylation at non-imprinted sites may also be important for expression of the paternal genome in the developing embryo. High throughput array technology has allowed the exploration of methylation across the whole genome, and has resulted in the finding that many non-imprinted genes are also linked to poor semen parameters [59,65].…”
Section: Dna Methylation In Sperm Function and Male Infertilitymentioning
confidence: 99%